AB0616 Cost analysis related to subcutaneous immunoglobulins in patients with inflammatory myopathies and immune-mediated chronic neuropathies. results of an open label study. (15th June 2017) - Vacchi, C; Sebastiani, M; Manfredi, A; Cassone, G; Campomori, F; Ferri, C
Abstract : Background: Intravenous Immunoglobulins (IVIg) represent a relevant treatment option in various immune-mediated disorders such as idiopathic inflammatory muscle diseases (IIMD), immune-mediated chronic neuropathies (IMCN), hematologic autoimmune diseases, Still disease, Felty syndrome, systemic lupus erythematosus, vasculitis, some organ-specific autoimmune disease, and atopic diseases. The IVIg treatment is expensive and need of hospital-based assistance for administration; the recent avaibility of home-therapy with subcutaneous immunoglobulins (SCIg) may significantly reduce costs and improve the patient's quality of life. Objectives: The primary objective was to perform an analysis of costs of SCIg administration in patients affected by IIMD or IMCN compared to that of previous IVIg treatments. Methods: We prospectively evaluated 6 consecutive patients (3 males and 3 females, mean age 65, 3 years, range 63 - 77), 2 affected by IIMD in the context of polymiositis and 4 by IMCN, 3 in the context of vasculitis and 1 in the context of undifferentiated connective tissue disease. All patients were previously treated with IVIg at the dosage of 2g/Kg monthly, (mean monthly dosage 143 g, range 98 – 160, average patient weight 71, 5 kg, range 49 - 80), with good clinical and humoral response. After a mean therapy duration of 49.8 months (range 12 – 125) all patients were shifted to SCIg at the dosage of 10 g twice a week (80 g monthly). Each patient was followed-up by humoral and clinical evaluation, including Medical Research Council (MRC) score to quantify muscle strength and INCAT Sensory Score to evaluate sensory symptoms. The costs of the two therapeutic strategies were also compared, excluding indirect costs (absences from work and productivity losses, transport and parking, health care sector costs). Results: In 5/6 patients, we observed the maintenance of clinical and humoral status after a mean follow-up of 21 months (range 4 - 51), in particular we observed a stability in MRC score in patients presenting loss of strenght and INCAT score in patients presenting sensory symptoms. Furthermore, the treatment with SCIg was well-accepted and preferred to IVIg by all patients. In one patient SCIg were discontinued after 2 weeks, because of the appearance of a haemorrhagic lesions nearby the injection site (in the same patient IVIg have been stopped because of a hypertensive crisis during the infusion). Direct cost associated to IVIg amount to 252€ for 5 g of immunoglobulins (7, 056€ monthly, considering a protocol of 2 g/kg/monthly and a patient-weight of 70kg), while direct costs associated to SCIg (20g weekly) amount to 6, 400€/monthly, with a saving of 656€/monthly and 7, 872€/yearly. In our case-series the annual saving was 9, 686.40€/patient (from 86, 486.40€ to 76, 800€, for IVIg and SCIg, respectively). Conclusions: Our experience suggests that the shift to SCIg from IVIg in patients affected by IIMD and IMCN is feasible, cost-effective, safe and well-accepted by patients. Further studies are needed to evaluate the effectiveness of SCIg in first-line therapy of these diseases. Disclosure of Interest: None declared